The average accumulated effective doses (1986-2016) for the population of the settlements of the Russian Federation attributed to the zones of radioactive contamination according to the Russian Federation government resolution «on the approval of the ... - G. Ya. Bruk; A. B. Bazyukin; A. A. Bratilova; A. Yu. Vlasov; A. V. Gromov; T. V. Zhesko; A. N. Kaduka; M. V. Kaduka; O. S. Kravtsova; I. K. Romanovich; K. A. Saprykin; V. S. Stepanov; et al. (Радиационная гигиена)
The Chernobyl accident in 1986 being one of the most large-scale radiation accidents in the world led to radioactive contamination of large areas in the European part of the Russian Federation and at the neighboring countries. Nowadays, there are adout 4000 settlements with the total population of more than 1.5 million in the radioactively contaminated areas of the Russian Federation. The Bryansk region is the most intensely contaminated region: thus, in the Krasnogorskiy district, there are still settlements with the level of soil contamination with cesium-137 exceeding 40 Ci/km2. Tula, Kaluga and Orel regions are also significantly affected. In addition to these four regions, there are ten other regions with the settlements located in the zones of radioactive contamination. After the Chernobyl accident, the affected areas have been divided into the zones of radioactive contamination. Belonging of the settlements to the one or another zone is determined by level of soil contamination with 137Cs and by value of the average annual effective dose that could be formed in the conditions of the absence of active measures of radiation protection and self-limitation with respect of the consumption of the local food products. The paper presents results of calculations of the average accumulated effective doses for the population. It is known that the most objective qualitative and quantitative index of the estimation of the actual radiation influence on the population of contaminated territories is the accumulated dose to population. In contrast to average annual effective exposure dose, which is estimated based on certain assumptions, the value of average accumulated dose is based on the doses which were actually received by inhabitants.